Upaya Meningkatkan Prestasi Belajar Akuntansi Melalui Metode Pembelajaran Tutor Sebaya Pada Siswa Kelas XI Ak.2 SMK St. Willibrodus Betun Tahun Pelajaran 2022/2023 - Gertrudis Basilisa Bere (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
The purpose of this study was to improve student achievement in class XI AK.2 SMK St. Willibrodus Betun in Accounting subject through the application of peer tutoring learning methods. The problems faced are the lack of student interest in accounting subjects, and the difficulty of maintaining focus during class. This has a negative impact on their academic performance. The proposed solution involves utilizing the peer tutoring method, whereby students receive assistance from their classmates in understanding accounting concepts. The research was conducted using the Classroom Action Research (CAR) method and involved 20 students as research subjects. The results showed that there was a significant increase in student achievement after the application of the peer tutoring method. In cycle I, 13 students successfully completed their studies with an average formative test score of 74.50 and a percentage of learning completeness of 65.00. In cycle II there was an increase in the number of students who completed their studies, with a total of 18 students. The average score of formative tests also increased to 88.00, and the percentage of complete learning reached 90.00. The conclusion drawn is that peer tutoring is an effective learning method in improving the academic achievement of Accounting students.